Barriers to Universal Design Adoption in Construction Projects (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Universal Design (UD) is increasingly recognized as an essential framework for promoting accessibility and inclusivity within the built environment; however, its integration into construction practice remains inconsistent, particularly in developing countries. This study examines the level of awareness of Universal Design among construction professionals and identifies key barriers affecting its adoption within construction projects in Nigeria. A quantitative cross-sectional survey design was employed using a structured questionnaire administered to construction professionals, including architects, engineers, quantity surveyors, contractors, project managers, builders, and procurement officers. A total of 102 valid responses were analyzed using descriptive statistical techniques, including frequencies, percentages, mean scores, and ranking analysis.The findings indicate a high level of professional awareness of Universal Design principles, with over 98% of respondents reporting familiarity with the concept and 85.3% indicating prior involvement in projects incorporating UD features. Despite this high awareness, consistent implementation remains limited. The most significant barriers identified include client priorities related to cost and aesthetics, perceived cost implications of UD features, limited client demand, insufficient technical training opportunities, and project time constraints. The results suggest that constraints affecting Universal Design adoption are influenced more by institutional and market driven factors than by lack of professional knowledge.In order to facilitate the broader incorporation of Universal Design principles in construction practice, especially in developing nation contexts, the study provides empirical evidence emphasizing the necessity of addressing structural hurdles within project delivery environments.